Pediatric intestinal pseudo-obstruction: Role of histopathology - Ana Luiza Melo dos Santos; Rafaela Wander Almeida Braga; Heinrich Bender Kohnert Seidler; Rodrigo Pinheiro de Abreu Miranda; Ivânia Itália Teixeira Salvador; Elisa de Carvalho (Elsevier, 2020)
Pediatric intestinal pseudo-obstruction (PIPO) is a rare and debilitating clinical disorder characterized by gastrointestinal motility dysfunction, resulting in symptoms suggestive of total or partial intestinal obstruction in the absence of any lumen-restricting or occlusive lesions. It is very similar to other bowel obstruction syndromes, favoring late diagnosis, chronic symptoms, poor nutritional status, poor quality of life and submission to various unnecessary surgeries. The investigation is based on excluding mechanical causes of intestinal obstruction, identifying underlying diseases, assessing possible drug induced disease and understanding the pathophysiological characteristics to determine the most appropriate therapy and prognosis.We report two cases of PIPO with distinct pathophysiology evidenced by histopathology; they were submitted to various surgical procedures and showed no response to clinical treatment, demonstrating the high morbidity and mortality of this disease. Histological evaluation was important in these cases to establish the definitive diagnosis, in addition to demonstrating continuing worsening.PIPO has a great impact on quality of life and high morbidity and mortality rates. Moreover, despite recent advances in its study, it still presents challenges regarding the proper understanding of its etiopathogenesis. In the cases presented, histopathology was essential for understanding the pathophysiology and progression of the disease.